Szkoły sióstr bazylianek w Jaworowie w okresie autonomii galicyjskiej 1867–1918 - Kudła, Lucyna (Biuletyn Historii Wychowania, 2018)
In the second half of the nineteenth century, Galicia became an autonomous province in Austria-Hungary. In addition to political reforms, changes in education were proposed. The Polish language and teaching Poland’s history were introduced to schools. Private schools for girls were also founded with the objective of raising their level of education and preparing them for academic studies. Schools run by religious congregations played a significant role here. The schools were run mainly by Catholic orders including the Basilian Sisters of the Ukrainian Greek Catholic Church (Ordo Sancti Basilii Magni). They had their convent in Jaworów in Galicia where they established an elementary school, a teachers’ school and a boarding school for girls. Ukrainian was the language of instruction. These religious schools operated according to the same principles as state schools, taught the same subjects and used the same textbooks. School authorities carried out inspections of religious schools on an annual basis. The schools enjoyed a good reputation and offered a high level of education.